ANALISIS OPTIMALISASI WAKTU LAYANAN POTONG RAMBUT PADA TAKILISH BARBER SHOP DENGAN MODEL ANTRIAN - Abidin, Yuliza; Rum Alim, Moch; Lestari, Rahayu (Oikonomia: Jurnal Manajemen, 2019)
This study aims to analyze the optimization of haircut service time at the Takilish Barber Shop using a single channel - single phase queue model. Primary data from observations and interviews with the concerned visitors used in this study were processed using Microsoft Excel with a single phase single channel queue structure and model A (MM/1) of queuing model. The results showed that the service at Takilish Barber Shop is not yet optimal, including in terms of service time, because of the high service level of the server, which causing a lot of free time that is not used optimally.